MYOPIA IN ADOLESCENTS IN MOUNTAINOUS AND FOOTHILL AREAS OF THE ANDIJAN REGION, THE CAUSES OF THE SPREAD (Multidisciplinary Journal of Science and Technology, 2026)
The reasons for the abandonment and rejuvenation of myopia in school children and adolescents, risk factors affecting the development of the disease, their origin, etiology, pathogenesis, clinic, diagnosis, complications and methods of their elimination in Pakhtaabad District, which is a mountainous region of the Andijan region, are widely studied in the modern direction.